THE INFLUENCE OF VOCABULARY AND GRAMMAR MASTERY ON STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXT (INFERENCE: Journal of English Language Teaching, 2026)
Reading plays an essential role in English as a Foreign Language (EFL) learning because it supports students’ understanding of vocabulary and grammar within texts. However, many junior high school students in Indonesia still experience difficulties in comprehending descriptive texts due to limited vocabulary and weak mastery of the simple present tense. Although previous studies have examined vocabulary and grammar separately, limited research has explored their combined influence on reading comprehension. This study investigates the effect of vocabulary mastery and simple present tense mastery on students’ comprehension of descriptive texts. A quantitative survey design was applied to students from public junior high schools in Banjarmasin selected through cluster random sampling. Three validated tests were administered: vocabulary, simple present tense, and reading comprehension. Multiple regression analysis revealed that both vocabulary and grammar mastery significantly affect reading comprehension, both individually and simultaneously, highlighting the importance of integrating linguistic components in reading instruction.
Keywords: vocabulary mastery; simple present tense; reading comprehension; descriptive text; EFL learning